If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -7) = 0 Reorder the terms: 7(-7 + x) = 0 (-7 * 7 + x * 7) = 0 (-49 + 7x) = 0 Solving -49 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + 7x = 0 + 49 Combine like terms: -49 + 49 = 0 0 + 7x = 0 + 49 7x = 0 + 49 Combine like terms: 0 + 49 = 49 7x = 49 Divide each side by '7'. x = 7 Simplifying x = 7
| -15n+18n+4n-20n=13 | | 1250=2x(300-x) | | 1/3x-4=8 | | 6x+16-5x=-3-10 | | g(-4t)=t-4 | | 9s+2s-8s=18 | | 21/14=w/4 | | 7x^7y^3/14x^5y^4 | | 3(x+4)=2x+20 | | 9/6=t/4 | | 4x-2(x-4)=-6+5x-4 | | 2(5-4x)=4(2-4x) | | a^2-8a+3=0 | | 20+5x+y=0 | | 9w-4w-3w+5w=14 | | 1.80*x=12 | | 7ln(x-2)=9 | | h=16x^2+30x+4 | | X^2/3-X-1/6=0 | | X^2/3-X-1/6=-0 | | x+x-x+x-x=17 | | 2.50x+108=1000 | | w=-29+1.4(32) | | 7a+(-10)-2a=1 | | 7lnx-2=9 | | G/3-7= | | 5x-1+67-x+7x+16=180 | | t-184.9=-109.3 | | .15x^2-14x+.125=0 | | 4x+3(x-7)-5x=34-19 | | 6250y-1840=2506 | | 10-8x=-2v+4x |